Analysis of wall excavation behaviour using advanced soil stress-strain models - Chen, Wan Sin (2015)
Of all the factors that contribute to the failure of deep excavation, the ability of the structural wall to resist lateral earth pressure plays a pivotal role and hence wall deflection has to be monitored closely. There are many available numerical programs to analyse the excavation works, such as FREW, WALLAP, SAGE CRISP and PLAXIS. Previous studies using WALLAP, SAGE CRISP and EXCAV 97 have been found to give reliable results. The focus of this project is to carry out back analysis using the finite element program PLAXIS 2D. Five local excavation case studies, namely Farrer Park and Kandang Kerbau, Rochor Complex, Syed Alwi Project, Lavender MRT Station and MOE Building were considered. Simple Mohr-Coulomb Model and advance Hardening Soil Model were used to conduct the analyses. By varying only the soft clay properties, the analyses were performed repeatedly by applying different E_50/c_u ratios until the wall deflections obtained from PLAXIS 2D were in good agreement with the measured wall deflections. The findings show that both the Mohr-Coulomb Model and Hardening Soil Model can give good agreement of wall deflections for the five case studies with E_50/c_u ratios that range from 200 to 300. The maximum strut forces at the final excavation stage were also compared.